(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Post-operative outcome of extradural haematoma (EDH) patients depends on the time interval of operation. Objectives: The purpose of the present study was to evaluate the role of time interval and surgical intervention in EDH. Methodology: This interventional study was carried out in the Department of Neurosurgery at Dhaka Medical College and Hospital, Dhaka, Bangladesh from July 2001 to July 2003 for a period of two (02) years. Patients with the history of head trauma admitted in Neurosurgery unit of Dhaka Medical College and Hospital which were being diagnosed as EDH both clinically and radiologically were included as study population. All patients were treated surgically and haematoma was evacuated. Outcome regarding neurological status, functional recovery, associated morbidity and mortality were assessed in each case as per Glasgow Outcome Scale and was compared between the two groups of patients who were treated surgically within 3rd day and 4th to 7th day after infliction of injury. The study population was devided into 4 groups on the basis of the consciousness level on admission of the patients. The EDH patietns who had GCS <5, 5 to 8, 9 to 12 and 13 to 15 were categorized as group I, II, III and IV respectively. On the basis of pre operative time interval, surgical intervention was done within 3 days of injury and from 4th to 7th day of injury. Craniotomy and craniectomy were done depending on patient’s condition and situation of haematoma. Result: A total 63 patients were included. During admission out of 63 patients majority of the patients were in the group III which was 29(46%) cases. During pre-operqative period out of 63 patients majority of the patients were in the group III which was 30(47.6%) cases. Out of 63 cases a total number of 40 cases were performed the surgery within 72 hours and the rest 23 patients were from 4th day to 7th day of injury. In group I at 8th POD, 3 death cases were recorded at 3rd day operation group and 2 cases at 4th to 7th cases. In group IV at 8th POD follow up good recovery was reported in 6 cases at 3rd day and 3 cases at 4th to 7th day. In group I after 1 month, 3 death cases were recorded at 3rd day operation group and 2 cases at 4th to 7th cases. In group IV after 1 month follow up good recovery was reported in 6 cases at 3rd day and 3 cases at 4th to 7th day; however, moderate disability was reported in 2 cases at 4th to 7th day. Conclusion: In conclusion mortality rate is reduced in patients with EDH who are treated in the earliest possible time after head injury Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 33-39